2007
DOI: 10.1590/s0104-56872007000400007
|View full text |Cite
|
Sign up to set email alerts
|

Memória de curto-prazo visual em crianças com distúrbio específico de linguagem

Abstract: Background: relationship between Specific Language Impairment (SLI) and visual short-term memory. Aim: to compare the performance of children with SLI to a control group of children with normal language development in tasks involving visual short-term memory. Method: subjects were 20 SLI children (ages 3;0 to 5;11), and 29 children with normal language development (ages 2;0 to 4;11), assessed in tasks of visual short-term memory involving picture recognition and localization recall of objects previously manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
2
6
0
1
Order By: Relevance
“…This study's results suggest that the children with SLI present diffi culties in operating visual stimuli, whether complex or simple, as is the case of the Rey Complex Figure and Memory for Faces, respectively. These fi ndings are in agreement with some studies (BuizaNavarrete et al, 2007;Hick et al, 2005aHick et al, , 2005bMarton, 2008;Menezes et al, 2007) that showed that children with SLI have a disadvantage in tasks with complex stimuli. In summary, the results found in this study partially support our fi rst hypothesis (H1).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study's results suggest that the children with SLI present diffi culties in operating visual stimuli, whether complex or simple, as is the case of the Rey Complex Figure and Memory for Faces, respectively. These fi ndings are in agreement with some studies (BuizaNavarrete et al, 2007;Hick et al, 2005aHick et al, , 2005bMarton, 2008;Menezes et al, 2007) that showed that children with SLI have a disadvantage in tasks with complex stimuli. In summary, the results found in this study partially support our fi rst hypothesis (H1).…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, even though these children present good non-verbal skills, defi cits in visual memory tasks, as reported in some studies (Buiza-Navarrete et al, 2007;Evans, Selinger, & Pollak, 2011;Hick, Botting, & ContiRamsden, 2005a, 2005bMarton, 2008;Menezes, Takiuchi, & Befi -Lopes, 2007), should be taken into account because they suggest visual cues are not being used to help the development of verbal aspects, as occurs in children with normal development. Indeed, the results of some studies, though some are contradictory, seem to indicate diffi culties in tasks in which stimuli are complex and/or in which there is a spatial dimension (Buiza-Navarrete et al, 2007;Hick et al, 2005aHick et al, , 2005bMarton, 2008;Menezes et al, 2007).…”
mentioning
confidence: 86%
“…In young children, significant group differences have been reported for children with SLI versus TD children on a variety of visuospatial storage and complex memory span tasks, including pattern recognition memory, paired associates learning, pattern recall, picture recognition, localization recall, spatial span, space visualization, and position-in-space but not for spatial recognition and a spatial WM search task (Bavin, Wilson, Maruff, & Sleeman, 2005;Hick, Botting, & Conti-Ramsden, 2005;Marton, 2008;Menezes, Takiuchi, & Befi-Lopes, 2007;Nickisch & von Kries, 2009). Longitudinal research by Hick et al (2005), moreover, has shown the performance of children with SLI (aged 3;03-4;05 years) on a pattern-recall task to develop more slowly than the performance of TD peers.…”
Section: Working Memory Impairments In Children With Slimentioning
confidence: 99%
“…Um estudo sobre a relação entre o Distúrbio Específico de Linguagem (DEL) e a memória de curtoprazo visual foi apresentado por Menezes et al (2007), que compararam o desempenho de 20 crianças com DEL e de 29 crianças em desenvolvimento normal de linguagem em tarefas envolvendo a memória de curtoprazo visual. De acordo com os resultados, as crianças com DEL apresentaram déficits em tarefas envolvendo memória de curto-prazo visual, sendo sugerido pelas autoras a discussão deste dado tanto para a compreensão da natureza do quadro, como para os processos de intervenção fonoaudiológica.…”
Section: Claudia Regina Furquim De Andrade Professora Titular Departaunclassified
“…A study about the relationship between Specific Language Impairment (SLI) and visual short-term memory was presented by Menezes et al (2007). This study compared the performance of 20 SLI children to a control group of 29 children with normal language development in tasks involving visual short-term memory.…”
Section: Claudia Regina Furquim De Andrade Professora Titular Departamentioning
confidence: 99%